PENGARUH JOB INVOLVEMENT, SOCIAL SUPPORT DAN STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PABRIK TAHU REJO MULYO PACITAN - Lucky Prastiyono; Siti Chamidah; Wahna Widhianingrum (Gapenas Publisher, 2022)
This study aims to determine the effect of job involvement, social support and work stress on employee turnover at the Rejo Mulyo Pacitan Tofu Factory. The population in this study were all permanent and non-permanent employees at the Rejo Mulyo Pacitan tofu factory, using total sampling as a sample. The data collection technique in this study was by distributing questionnaires with negative statements to all employees of the Rejo Mulyo Pacitan tofu factory. The analytical method used in this research is multiple linear regression. The results showed that 1) Job Involvement had a positive effect on Turnover Intention with a significance of 0.007. 2) Social Support has a positive effect on Turnover Intention with a significance of 0.000. 3) Job stress has a positive effect on Turnover Intention with a significance of 0.004. 4) independent variables simultaneously affect Turnover Intention by 70.0% while 30.0% is influenced by other variables